Electrical, optical and structural properties of Al-doped ZnO thin films grown on GaAs(111)B substrates by pulsed laser deposition - Weigand, Christian; Crisp, Ryan; Ladam, Cécile; Furtak, Tom; Collins, Reuben; Grepstad, Jostein; Weman, Helge (Thin Solid Films, 2013)
We report on the characteristics of Al-doped ZnO thin films (AZO) grown on GaAs(111)B substrates using pulsed laser deposition. The influence of ambient gas composition, overall pressure, and growth temperature on the electrical, structural and optical properties of 100 nm-thin films grown from a ZnO target with 2 wt.% Al were investigated. Growth in a 1 Pa pure O-2 ambient was found to be superior to films grown in Ar ambient or vacuum with respect to their electrical properties. As-grown AZO films showed a low resistivity on the order of 10(-4) Omega cm. Post-deposition annealing in-situ showed no improvement of the transport properties, irrespective of annealing temperature and ambient gas. At high substrate temperatures, the interaction with the GaAs(111)B substrate seemed to affect the growth and conductivity of the AZO films. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Al-doped ZnO; Transparent conductive oxide; Pulsed laser deposition; GaAs substrate